DAMPAK STRUKTUR MODAL PADA SENSITIVITAS PENERAPAN KOMPENSASI OPSI SAHAM KARYAWAN TERHADAP KINERJA - Nur Fadjrih Asyik (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
This study aims to test whether the management that receive compensation in the form of stock options having an positive impact on company performance. This study considers the external performance measurement by identifying Cumulative Abnormal Return (CAR). In addition, this study aims to test whether the company's capital structure affects the sensitivity level of employee stock option compensation and firm performance. Capital structure is measured with debt to equity ratio. The result indicates that the proportion of Employee Stock Option Plan (ESOP) influence company performance in accordance with the predictions. This shows that the more stock options offered to employees then came a sense of belonging which resulted in more motivated managers to improve company performance. Furthermore, the higher the market performance of companies that can be achieved, the higher the profit (gain) will be obtained by the recipient of stock options. In addition, this study also shows that the impact of stock option grants at the company's performance declined with the greater capital structure of liability. This shows that the capital structure of liabilities will lower the sensitivity level of employee stock option compensation and firm performance. The higher the company's liabilities would reduce the rights of the owner of the dividends each period in accordance with the ownership of shares held since the company must take into account the interest costs to be paid to the creditor.